1970
DOI: 10.1038/bjc.1970.35
|View full text |Cite|
|
Sign up to set email alerts
|

Development of Injection-site Sarcomata in Rats: A Study of the Early Reactive Changes Evoked by a Carcinogenic Nitrosoquinoline Compound

Abstract: SUMMARY.-The early changes induced by a carcinogenic nitrosoquinoline compound (NTDQ) have been studied in the subcutaneous tissues of 88 rats. An initial acute inflammatory response is quickly replaced by a distinctive granuloma which is established by 10 days and persists indefinitely-a sequence which takes place both in adult and in newborn animals. Its main components-histiocytes, multinucleate giant cells and granulation tissue-are described in detail and the formation of giant cells by fusion from adjace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1971
1971
2002
2002

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…17 In the 1960s, Carter et al reported on the early development of injection-site sarcomas in rats. [18][19][20] They studied the histopathological changes occurring after subcutaneous and intraperitoneal injection of polymerised nitroso-rubber compound 18 and after intramuscular injection of iron-dextran. 19 Three stages of development were tentatively de ned.…”
Section: Discussionmentioning
confidence: 99%
“…17 In the 1960s, Carter et al reported on the early development of injection-site sarcomas in rats. [18][19][20] They studied the histopathological changes occurring after subcutaneous and intraperitoneal injection of polymerised nitroso-rubber compound 18 and after intramuscular injection of iron-dextran. 19 Three stages of development were tentatively de ned.…”
Section: Discussionmentioning
confidence: 99%
“…THE pathological effects of a polymerised nitrosoquinoline compound NTDQ (N-nitroso-2,2,4-trimethyl-l ,2-dihydroquinoline) have been under investigation in this department. Although it was originally suspected to be a carcinogen, NTDQ has been shown to produce few local tumours after subcutaneous injection in the rat (Carter and Roe, 1968); an interesting series of histopathological changes has, however, been found at the site of injection of the material (Carter, 1969;Carter, Birbeck and Roberts, 1970).…”
Section: Plate CVIIImentioning
confidence: 99%
“…
PLATE CVIIITHE pathological effects of a polymerised nitrosoquinoline compound NTDQ (N-nitroso-2,2,4-trimethyl-l ,2-dihydroquinoline) have been under investigation in this department. Although it was originally suspected to be a carcinogen, NTDQ has been shown to produce few local tumours after subcutaneous injection in the rat (Carter and Roe, 1968); an interesting series of histopathological changes has, however, been found at the site of injection of the material (Carter, 1969;Carter, Birbeck and Roberts, 1970).NTDQ initially evokes a granuloma which persists for many months; local changes which have been interpreted as early neoplasms eventually appear and some progress to form macroscopic sarcomas. Among the components of these granulomata are many large multinucleate giant cells.
…”
mentioning
confidence: 99%